Employability and Skill Set of Newly Graduated Engineers in India - Blom, Andreas; Saeki, Hiroshi (2012)
Skill shortage remains one of the major constraints to continued growth of the Indian economy. This employer survey seeks to address this knowledge-gap by answering three questions: (i) Which skills do employers consider important when hiring new engineering graduates? (ii) How satisfied are employers with the skills of engineering graduates? and (iii) In which important skills are the engineers falling short? The results confirm a widespread dissatisfaction with the current graduates -- 64 percent of employers hiring fresh engineering graduates are only somewhat satisfied with the quality of the new hires or worse. After classifying all skills by factor analysis, the authors find that employers perceive Soft Skills (Core Employability Skills and Communication Skills) to be very important. Skill gaps are particularly severe in the higher-order thinking skills ranked according to Bloom's taxonomy. In contrast, communication in English has the smallest skill gap, but remains one of the most demanded skills by the employers. Although employers across India asks for the same set of soft skills, their skill demands differ for Professional Skills across economic sectors, company sizes, and regions. These findings suggest that engineering education institutions should: (i) seek to improve the skill set of graduates; (ii) recognize the importance of Soft Skills, (iii) refocus the assessments, teaching-learning process, and curricula away from lower-order thinking skills, such as remembering and understanding, toward higher-order skills, such as analyzing and solving engineering problems, as well as creativity; and (iv) interact more with employers to understand the particular demand for skills in that region and sector.